Movie Induced Tourism in the Young Millennials Tourist Segment - Ayu Ananda; Azizah Salsabila Nugraha; Annisa Rachmah Fujianti; Eko Susanto (Politeknik Negeri Bandung, 2021)
This research is motivated by the considerable potential and market share of millennials as a tourism target market. The promotion strategy of a tourist destination is carried out through innovative media, one of which is through movie media or empirically known as the concept of Movie Induced Tourism. This research was conducted to determine the effect of movies on millennial tourist visits, applying descriptive quantitative research methods. Questionnaires were used as data collection techniques to obtain primary data and through journals and e-book to get secondary data. SEM-PLS has been applied to measure relationships between variables and research models. The results of this study are that movies attributes can have a significant positive effect on personal connections and AIDA Model.